Visuoperceptual Impairment in Children with NF1: From Early Visual Processing to Procedural Strategies - Sara Bulgheroni; Matilde Taddei; Veronica Saletti; Silvia Esposito; Roberto Micheli; Daria Riva (Behavioural Neurology)
Visual-spatial impairment has long been considered a hallmark feature of neurofibromatosis type 1 (NF1). No study investigating the cognitive and neuropsychological profile of NF1 used the Rey Complex Figure Test (RCFT) task as the primary measure of visual-perceptual abilities taking into consideration all functions involved including the strategic processing style. We compared 18 children with NF1, 17 siblings (S), and 18 typically developing children (TD) at intelligence scale and RCFT copy, recall, and recognition trials; we also evaluated the copy strategy as a measure of a visual-processing style. Children with NF1 had normal total IQ, with cognitive weaknesses in the perceptual organization and working memory in line with the existing literature. At the RCFT copy, immediate and delay recall scores are significantly lower in NF1 than S and TD, while recognition is in the normal range in all groups. Copy style was poor and less efficient in children with NF1 and correlated to copy and recall ability, but the effect of the group in the RCFT copy and recall remained significantly controlling for strategic approach. The present study confirms visuospatial impairment in children with NF1, due to a deficit in perceptual analysis of shape and their spatial features, in visuomotor integration efficiency and strategies, in recall memory, while recognition memory is preserved. A more configural/holistic style may facilitate both the visual-perceptual and visuomotor ability and the recall process. Visuoperceptual impairment in NF1 seems to be a unified process from early visual processing to higher order functions (planning, strategy, and executive functioning).